Myth = Mithya - Pattanaik, Devdutt (Penguin Books India, 2006)
Hindu mythology is full of variety. There are 330 million gods. There are gods, goddesses, spirits, personal gods, household gods and gods of space and time. There are gods for each caste, and guardian gods who look after the artisans. There are gods who are protective of the nature, living in trees, and other who take animal form. Some are fond of minerals, some find meaning in geometrical form. Then there are numerous demons, each of which has its own story of rise and fall. Yet, there is no central Devil to this mythology, no head honcho on whom to lay the blame for the demons and their ravaging. In this book, Devdutt Pattanaik seeks to help readers understand many aspects of Hindu mythology. He selects a few stories which speak for themselves, helping readers understand why Yudhishthira alone went to heaven while his brothers were doomed to hell. He throws light on Rama s status as the model king despite his banishment of Sita to the woods. He also explains why Gauri and Kali are the same, even though one nourishes while the other slays. This book is a definite read for all those who wish to understand more about Hindu mythology